Future prospects for anti-cytokine treatment. (1st November 2000) - Feldmann, Marc; Miotla, Jadwiga; Paleolog, Ewa; Williams, Richard; Malfait, Anne-Marie; Taylor, Peter; Brennan, Fionula M; Maini, Ravinder N
Abstract : The era of anti-cytokine treatment in rheumatology has just begun. The first generation therapeutic agents, biological agents that block tumour necrosis factor α such as monoclonal antibodies or receptor Ig fusion proteins are safe and effective, and so this has generated much interest in how to increase the benefit or deliver it more cost effectively. This article provides a personal view of the coming trends in anti-cytokine treatment. Which of these will be realised in the future will be of interest.